AWARENESS AND USAGE OF ICT TOOLS BY THE LIBRARY PERSONNEL AT THE NIMBE ADEDIPE LIBRARY, FEDERAL UNIVERSITY OF AGRICULTURE, ABEOKUTA, OGUN STATE, NIGERIA. (2013)
This paper assesses the level of awareness and extent of utilisation of information and communication tools by library personnel in the Nimbe Adedipe Library, Federal University of Agriculture, Abeokuta, Ogun State. It investigates the pattern of usage, the perceived benefit and constrains of ICT tools utilization in the library. A researcher- designed structured questionnaire and interview was used to gather data. The sample population consisted of 42 library personnel drawn from the main campus library, college libraries and mini campus library of FUNAAB. Five research questions were raised and the findings revealed that librarians in the study have a sound awareness about the importance of ICT in their libraries. The reasons may include an understanding of the benefits of ICT. The results revealed further that librarian training and knowledge of ICT influenced their attitudes toward it. Low bandwidth and poor connectivity constituted problems to effective utilisation of ICT. The study concludes that the Use of ICT has come to stay in Nigerian University libraries and strongly recommends automation and Internet connectivity in libraries with corresponding training programmer to enable librarians acquire adequate skills and knowledge of computer potentials for the provision of high quality library services, especially in the areas of research and teaching. It was further recommended that Adequate and functional ICT tools should be made available at the library so as to facilitate effective service delivery at the library.